Penyelesaian Sengketa Perbankan Syariah di Pengadilan Agama - Ramlah Ramlah (NALAR FIQH: Jurnal Hukum Islam, 2012)
In the era of reformation Religious Courts authority increases in economic shari'a as stipulated in Article 49 Amendment UU No. 3 of 2006 on Islamic Courts. In this case if the dispute Shariah banking occurs due to a dispute aqad (agreement) between the parties which resolve is the governing body of Arbitration, while the decision of peace carried out by the Islamic court.